(untitled) (Experimental biology, 2015)
Phytopathological, genetic and breeding study of resistance to leaf rust in isogenic lines and differentials was conducted. 5 isogenic lines of wheat showed exceeding in complex of productivity traits. On the basis phytopathological study most of isogenic lines resistant to leaf rust have been shown. The data obtained are valuable in wheat rust improvement breeding programs.